Rancang Bangun Sistem Monitoring Arus, Tegangan, Kecepatan Putar Turbin dan Suhu Berbasis IoT Pada Pembangkit Listrik Tenaga Uap Mini Skala Laboratorium - Muhammad Ibrahim Alfitroh; Humaidillah Kurniadi Wardana (Rekayasa, 2023)
The PLTU monitoring system developed in this study will be in the form of a monitoring system for temperature, current, voltage, turbine speed on a laboratory scale mini PLTU created using the blynk application and displayed on a smartphone. The research method used is in the form of testing a monitoring system comparing the prototype with standard gauges to determine the percentage of the measurement error, readings of type K and MAX6675 thermocouples, Lm393 sensors, DC voltage sensors, ACS712 sensors. The results of the measurement of the steam temperature sensor have an average percentage error of 0.03%, the turbine rotation sensor has an average percentage error rate of 0.01%, DC voltage sensor has an average error percentage rate of 0.07%, DC current sensors have an average percentage error rate of 0.10%.